Plasma Transfusion: History, Current Realities, and Novel Improvements. Issue 5 (November 2016) - Watson, Justin J. J.; Pati, Shibani; Schreiber, Martin A.
Abstract : ABSTRACT: Traumatic hemorrhage is the leading cause of preventable death after trauma. Early transfusion of plasma and balanced transfusion have been shown to optimize survival, mitigate the acute coagulopathy of trauma, and restore the endothelial glycocalyx. There are a myriad of plasma formulations available worldwide, including fresh frozen plasma, thawed plasma, liquid plasma, plasma frozen within 24 h, and lyophilized plasma (LP). Significant equipoise exists in the literature regarding the optimal plasma formulation. LP is a freeze-dried formulation that was originally developed in the 1930s and used by the American and British military in World War II. It was subsequently discontinued due to risk of disease transmission from pooled donors. Recently, there has been a significant amount of research focusing on optimizing reconstitution of LP. Findings show that sterile water buffered with ascorbic acid results in decreased blood loss with suppression of systemic inflammation. We are now beginning to realize the creation of a plasma-derived formulation that rapidly produces the associated benefits without logistical or safety constraints. This review will highlight the history of plasma, detail the various types of plasma formulations currently available, their pathophysiological effects, impacts of storage on coagulation factors in vitro and in vivo, novel concepts, and future directions.